Quantum Organizations with Islamic Way Forward - Yazdani, Naveed; Abbas, Rana Zamin; Hameed, Kamran (Journal of Management and Research, 2021)
Firstly, this paper describes a phenomenon of transnational organization and general condition of world and ‘man in the world’. For developing a comprehensive framework, it presents authentic literature review beginning from modernity to post modernity using the hermeneutic-interpretivism research tradition to show the similarities between modernism and post modernism. By revealing the missing link in the quantum paradigm of ralph Kilmann (scholar of quantum organization) on one hand, it develops the possibility of reviving revealed knowledge back into the main frame knowledge of organization theory, on the other hand. By raising and addressing the question of how can the revealed knowledge addresses the current economic dilemma, the paper describes the three lenses available used to understand natural world, socio economic world and behavioral world in Newtonian verses quantum assumptions on organization theory along with their implications. For cross fertilization of ideas and better understanding of God, cosmos and human it presents an alternative of Islamic way forward suggested by scholarly views from East and West. To further substantiate, it presents the stunning insights from the renowned wisdom traditions (pragmatic civilizations) to highlight why religions matter to show (the levels of reality and levels of selfhood as well as relationship between Necessity being and contingent being), responding the situation of power and domination prevalent in organizing world by suggesting historical/civilizational ethical mode and adopting psycho, spiritual-pragmatic approach with holistic world view (Big picture).